Pengaruh Pemberian Aroma Terapi Lavender Dan Musik Klasik Lullaby Terhadap Tingkat Kecemasan Pasien Pre Operasi Sectio Caesarea Di SMC RS Telogorejo - Rizki Dwi Mentari; Anis Ardiyanti; Diffa Risqa Arisdiani (Jurnal Ventilator, 2023)
Sectio caesarea (SC) is a surgical procedure performed to give birth to a baby. Caesarean sectio action can cause anxiety in preoperative mothers. Anxiety can cause discomfort, so therapy is needed to reduce anxiety levels. Giving lavender aromatherapy and lullaby classical music can reduce anxiety. This study aims to determine the effect of lavender aromatherapy and lullaby classical music on the anxiety level of preoperative sectio caesarea mothers at SMC Telogorejo Hospital. This type of research is a quasi experiment with a pretest-posttest design without a control group design, the consencutive sampling used is accidental, with a total sample of 40 respondents. The characteristics of the respondents were obtained by all respondents aged 20-30 years by 40 (100%), tertiary education by 30 respondents (75%), primigravida 21 respondents (52.5%). Wilcoxon test results, obtained a p-value of 0.000. So it can be concluded that giving lavender aromatherapy and lullaby classical music can reduce the level of anxiety in preoperative sectio caesarea mothers. For future research, it is expected to pay attention to the duration and the most effective time to reduce anxiety levels after being given an intervention.